Multimedia fate of petroleum hydrocarbons in the soil: Oil matrix of constructed biopiles - Coulon, Frederic; Whelan, Michael J.; Paton, Graeme I.; Semple, Kirk T.; Villa, Raffaella; Pollard, Simon J. T. (Elsevier Science B.V., Amsterdam., 2010)
A dynamic multimedia fugacity model was used to evaluate the partitioning and fate of petroleum hydrocarbon fractions and aromatic indicator compounds within the soil: oil matrix of three biopiles. Each biopile was characterised by four compartments: air, water, soil solids and non-aqueous phase liquid (NAPL). Equilibrium partitioning in biopile A and B suggested that most fractions resided in the NAPL, with the exception of the aromatic fraction with an equivalent carbon number from 5 to 7 (EC5-7). In Biopile C, which had the highest soil organic carbon content (13%), the soil solids were the most important compartment for both light aliphatic fractions (EC5-6 and EC6-8) and aromatic fractions, excluding the EC16-21 and EC21-35. Our starting hypothesis was that hydrocarbons do not degrade within the NAPL. This was supported by the agreement between predicted and measured hydrocarbon concentrations in Biopile B when the degradation rate constant in NAPL was set to zero. In all scenarios, biodegradation in soil was predicted as the dominant removal process for all fractions, except for the aliphatic EC5-6 which was predominantly lost via volatilization. The absence of an explicit NAPL phase in the model yielded a similar prediction of total petroleum hydrocarbon (TPH) behaviour; however the predicted concentrations in the air and water phases were significantly increased with consequent changes in potential mobility. Further comparisons between predictions and measured data, particularly concentrations in the soil mobile phases, are required to ascertain the true value of including an explicit NAPL in models of this kind.